Investigation of Teaching Factory (TEFA) Implementation in Vocational Education - Suyitno Suyitno (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this research is: 1) investigating the implementation of the Teaching Factory in the Department of Automotive Light Vehicle Engineering at SMK Taman Karya Madya Teknik Kebumen in a systematic manner, 2) understanding the factors that support the implementation of Teaching Factory at SMK Taman Karya Madya Teknik Kebumen's Department of Automotive Light Vehicle Engineering, and 3) Recognizing the factors impeding the implementation of the Teaching Factory at SMK Taman Karya Madya Teknik Kebumen's Department of Automotive Light Vehicle Engineering.This study is a type of descriptive study. The method used is qualitative. Data collection techniques are carried out through 1) observation, 2) interview, and 3) documentation activities. The stages of description, reduction, and selection are all part of the research procedure.The study results that, overall, the management of the Teaching Factory implementation in the Department of Automotive Light Vehicle Engineering, the Teaching Factory workshop service unit at SMK Taman Karya Madya Teknik Kebumen has been well implemented. It has followed the concepts and objectives of the Teaching Factory itself in implementing the Teaching Factory workshop business unit as a manifestation of the Teaching Factory form. The involvement of students in the management of Teaching Factory implementation in the Department of Automotive Light Vehicle Engineering, the Teaching Factory workshop service unit at SMK Taman Karya Madya Teknik Kebumen is following the teaching factory learning concept in this case. Students are only involved in the implementation of the Teaching Factory in the Automotive Light Vehicle Engineering Department. Meanwhile, it is still carried out by the management of the Teaching Factory in the Automotive Light Vehicle Engineering Department, the Teaching Factory workshop service business unit at SMK Taman Karya Madya Teknik Kebumen in terms of Planning, Organizing, and Supervision.